2005
DOI: 10.1111/j.1399-3038.2005.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of modified Mai‐Men‐Dong‐Tang for treatment of allergic asthma

Abstract: The aim of this study was to evaluate the efficacy and safety of a Chinese herbal formula modified Mai-Men-Dong-Tang (mMMDT) for treatment of persistent, mild-to-moderate asthma. A total of 100 asthmatic patients were enrolled and assigned to three treatment groups in this double-blind, randomized, placebo-controlled clinical trial. Over a period of 4 months, patients in groups A and B received 80 and 40 mg/kg/day of mMMDT, while those in group C received a placebo. Efficacy variables included changes in force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 14 publications
1
76
0
4
Order By: Relevance
“…In 2005, Hsu et al [18] reported results of a clinical investigation of a complementary TCM therapy for asthma. This study evaluated the efficacy and safety of a Chinese herbal formula, modified Mai Men Dong Tang (mMMDT) for treatment of persistent, mild-to-moderate asthma.…”
Section: Modified Mai Men Dong Tang (Mmmdt)mentioning
confidence: 99%
“…In 2005, Hsu et al [18] reported results of a clinical investigation of a complementary TCM therapy for asthma. This study evaluated the efficacy and safety of a Chinese herbal formula, modified Mai Men Dong Tang (mMMDT) for treatment of persistent, mild-to-moderate asthma.…”
Section: Modified Mai Men Dong Tang (Mmmdt)mentioning
confidence: 99%
“…There were no significant changes in sIgE, sIgG 4 , sIgE/sIgG 4 ratio, and IL-10 and IFN-γ levels between treatment groups (Table 4). A significant increase in IL-5 was observed in the active group, but no change was seen in the placebo group.…”
Section: Immunological Test Resultsmentioning
confidence: 90%
“…[17] Comparison of categorical data was performed with Fisher's exact test with a 2-tailed p value, while comparison of continuous data was performed with a t-test. Analysis of Covariance (ANCOVA) models were used to assess whether the change from baseline to post-therapy in various outcome variables (sIgE, sIgG 4 , IL-5, IL-10, IFN-γ, basophil activation, SPTs) differed between treatment groups. [18] The change in the outcome was the dependent variable and the following were independent variables: treatment group, baseline value, treatment-by-baseline interaction, adherence to treatment, and clinical center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsu et al (18) tested modified Mai Men Dong Tang (mMMDT, 5 herbs) for treatment of persistent, mild-to-moderate asthma in children. (Table I).…”
Section: Modified Mai Men Dong Tang (Mmmdt)mentioning
confidence: 99%